The last attempt of regulating insane offenders in Argentina: The Draft Penal Code elaborated by Eusebio Gómez and Jorge Eduardo Coll in 1938 - Roldán Cañizares, Enrique; Rosso, Matías (GLOSSAE. European Journal of Legal History, 2023)
Criminological positivism had an enormous repercussion and impact on criminal law in Argentina, although it is true that its postulates, although accepted by a large number of criminologists, did not manage to cross the walls of libraries and study rooms, being relegated to the academic world. However, there was a draft penal code drawn up by Eusebio Gómez and Jorge Eduardo Coll that was built on the principles of criminological positivism, which is why we have decided to rescue and study it. In this specific case, we have focused on the regulation of insane offenders, which were not only regulated in greater detail than in previous codes or projects, but were also placed in relation to dangerousness, which demonstrates not only the positivist affiliation of this draft code, but also the importance that the authors gave to the regulation of insane offenders in the interests of the criminal justice system.